The Effect Of Whole Language Approach On The Improvement Of Early Reading Ability Of Grade IV Students With Intellectual Disabilities At SLB Negeri Sukharjo In The Academic Year 2022/2023 - Munawir Yusuf; Priyono Priyono; Putri Wahidah Nuril Hayati (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2023)
This study aims to: Determine the effect of the Whole Language Approach method on improving the initial reading ability of elementary school-age students with intellectual disabilities in SLB Negeri Sukoharjo for the 2022/2023 academic year. This research is a pre-experimental quantitative research with a research design of one group pretest posttest. Data sources of this study include the results of oral assessments of students' beginning reading skills. The validity test technique used is the validity of the content. Data analysis using the Wilcoxon sign ranks test. The result of this study is that there is a significant impact of the application of the whole language approach on improving the initial reading ability of grade IV students with intellectual disabilities at SLBN Sukoharjo. And the conclusion is Whole Language Approach can giving effect to increasing oral assessments of students' beginning reading skills for 4th grade elementary student with intellectual disability in SLB Negeri Sukoharjo.